2021
DOI: 10.1177/0002716220987830
|View full text |Cite
|
Sign up to set email alerts
|

Putting Homelessness in Context: The Schools and Neighborhoods of Students Experiencing Homelessness

Abstract: The number of K–12 students experiencing homelessness is increasing across the country. Schools may serve as sources of support and stability for homeless children, but little is known about the types of schools that homeless students attend or about the communities in which they live. We investigate the context of student homelessness in Los Angeles by analyzing student-level administrative data from the Los Angeles Unified School District and publicly available data on neighborhoods and schools from school y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
(29 reference statements)
1
6
0
Order By: Relevance
“…While I show discrepancies in child and youth homelessness due to data availability, similar discrepancies likely exist in overall homelessness, particularly across subpopulations (e.g., sheltered vs. unsheltered) and internationally (Dhaliwal et al 2021; Parolin 2021; Toro 2007). Given the recent increase in scholarly work on aggregate-level studies of homelessness across fields—economics, education, public policy, and others (O’Flaherty 2019)—clearly defining who counts as homeless in research, such as through the ETHOS, must occur to obtain an understanding of the causes of homelessness and which interventions help.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…While I show discrepancies in child and youth homelessness due to data availability, similar discrepancies likely exist in overall homelessness, particularly across subpopulations (e.g., sheltered vs. unsheltered) and internationally (Dhaliwal et al 2021; Parolin 2021; Toro 2007). Given the recent increase in scholarly work on aggregate-level studies of homelessness across fields—economics, education, public policy, and others (O’Flaherty 2019)—clearly defining who counts as homeless in research, such as through the ETHOS, must occur to obtain an understanding of the causes of homelessness and which interventions help.…”
Section: Discussionmentioning
confidence: 71%
“…More recently, two studies estimate differences in homelessness based on definition. First, Dhaliwal et al (2021) studied the schools and neighborhoods of students experiencing homelessness. While they found community characteristics to be similar for all homeless and doubled-up students, they did find, compared to non-doubled-up but homeless students, doubled-up students were less likely to be Black, more likely to be Latinx or immigrants, and less likely to exit the district.…”
Section: Defining Homelessnessmentioning
confidence: 99%
“…In other work on LAUSD, we found that homeless students (who are typically doubled up, rather than unsheltered) are more likely to be marginalized on a variety of indicators (e.g., Black, Latinx, eligible for special education (SPED) services, immigrants), to be clustered in schools and neighborhoods with higher concentrated disadvantage (e.g., lower achieving schools, higher proportions of students of color, FRL-eligible students), to have higher levels of school and neighborhood mobility, and to exit the district more often than students who are not homeless (Dhaliwal et al, 2021).…”
Section: The Lausd Context: Homeless Student Identification and Suppo...mentioning
confidence: 99%
“…Homelessness. High housing costs are clearly a leading cause of homelessness (Nisar et al, 2019;JCHS, 2019), and children experiencing homelessness suffer from an array of negative educational outcomes, including worse attendance, low academic achievement, and social isolation (Dhaliwal et al, 2021;Miller, 2011). According to Miller's (2011) systematic review of the research literature on homelessness and educational outcomes, however, there has been some debate within the scholarship as to whether the outcomes are due to experiencing homelessness, or due to the low-income status that accompanies homelessness.…”
Section: Indirect Pathway 1: Residential and School Mobility Caused B...mentioning
confidence: 99%